Single-parameter spin-pumping in driven metallic rings with spin-orbit coupling - Ramos, J. P. (2014)
We consider the generation of a pure spin-current at zero bias voltage with a single time-dependent potential. To such end we study a device made of a mesoscopic ring connected toelectrodes and clarify the interplay between a magnetic flux, spin-orbit coupling, and non-adiabatic driving in the production of a spin and electrical current. By using Floquet theory, weshow that the generated spin to charge current ratio can be controlled by tuning the spin-orbitcoupling.